Shepherding with Love: Apostle Peter's Guidance from 1 Peter 5:1-4 for Christian Educators - Sutarti, Sutarti (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
Jesus Christ, as the Chief Shepherd (1 Peter 5:4), serves as the primary model for spiritual leaders in fulfilling their pastoral duties. In John 10:11, Jesus is portrayed as a faithful Shepherd who lovingly cares for His sheep and is even willing to sacrifice His life for them. After His resurrection, Jesus appeared to His disciples and gave a special commission to Peter to undertake the pastoral task (John 21:15-17), emphasizing that this duty is a sacred calling entrusted by God to be carried out according to His will. This study aims to examine the Apostle Peter's advice on shepherding in 1 Peter 5:1-4 and its relevance for Christian Educators. The research employs a qualitative method using literature review and biblical text analysis to identify leadership principles in shepherding. The findings reveal that the Apostle Peter's advice includes four key principles for a shepherd's ministry: serving willingly, being sincere in devotion, exhibiting humility, and being a good example to the congregation. These principles are considered essential for cultivating the spirituality of service for a Christian Educator who acts as a lecturer or teacher. In conclusion, the Apostle Peter's advice on shepherding provides guidance for spiritual leaders to fulfill their roles as Christian Educators in accordance with Christ's example, characterized by love, integrity, and dedication.